Finance for Development : Trends and Opportunities in a Changing Landscape - Adugna, Abebe; Castro, Rocio; Gammara, Boris; Migliorisi, Stefano (World Bank, Washington, DC, 2017)
Over the past couple of decades, global financing for development has changed dramatically. The biggest shifts have been the rapid increase of net private financing flows to developing countries, in particular to middle-income countries (MICs); the sustained growth of official development assistance (ODA) from Development Assistance Committee (DAC) members, even excluding debt relief; the emergence of MICs as growth poles and sources of ODA with different approaches to aid delivery than those of DAC donors; and the expanded role of private aid. In addition, past trends of proliferation, fragmentation and earmarking of aid have continued. This paper reviews broad trends in global financing for development, with a focus on ODA and the growing importance of new development partners such as the so-called BRICS. In this context, it discusses the implications of this changing landscape for aid effectiveness and the role of ODA going forward.